Biomechanical demands of the 2-step transitional gait cycles linking level gait and stair descent gait in older women. Issue 16 (16th December 2015) - Alcock, Lisa; O׳Brien, Thomas D.; Vanicek, Natalie
Abstract: Stair descent is an inherently complex form of locomotion posing a high falls risk for older adults, specifically when negotiating the transitional gait cycles linking level gait and descent. The aim of this study was to enhance our understanding of the biomechanical demands by comparing the demands of these transitions. Lower limb kinematics and kinetics of the 2-step transitions linking level and descent gait at the top (level-to-descent) and the bottom (descent-to-level) of the staircase were quantified in 36 older women with no falls history. Despite undergoing the same vertical displacement (2-steps), the following significant ( p <.05) differences were observed during the top transition compared to the bottom transition: reduced step velocity; reduced hip extension and increased ankle dorsiflexion (late stance/pre-swing); reduced ground reaction forces, larger knee extensor moments and powers (absorption; late stance); reduced ankle plantarflexor moments (early and late stance) and increased ankle powers (mid-stance). Top transition biomechanics were similar to those reported previously for continuous descent. Kinetic differences at the knee and ankle signify the contrasting and prominent functions of controlled lowering during the top transition and forward continuance during the bottom transition. The varying musculoskeletal demands encountered during each functional sub-task should be addressed in falls prevention programmes with elderly populations where the greatest clinical impact may be achieved. Knee extensor eccentric power through flexion exercises would facilitate a smooth transition at the top and improving ankle plantarflexion strength during single and double limb stance activities would ease the transition into level gait following continuous descent.